1994
DOI: 10.1136/gut.35.9.1197
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal adaptation to aspirin induced gastric damage in humans. Studies on blood flow, gastric mucosal growth, and neutrophil activation.

Abstract: The gastropathy associated with the ingestion of non-steroidal anti-inflammatory drugs (NSAIDs) such as aspirin is a common side effect of this class of drugs, but the precise mechanisms by which they cause mucosal damage have not been fully explained. During continued use of an injurious substance, such as aspirin, the extent of gastric mucosal damage decreases and this phenomenon is named gastric adaptation. To assess the extent of mucosal damage by aspirin and subsequent adaptation the effects of 14 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…Konturek et al 68) reported that gastric mucosa increases its resistance to damage caused by aspirin during repeated administration of aspirin. Jin et al 69) observed that the increase in HSP (mainly HSP70) expression correlated with mucosal resistance that observed after repeated administration of aspirin.…”
Section: -1 Expression Of Hsps In Gastrointestinal Tractmentioning
confidence: 99%
“…Konturek et al 68) reported that gastric mucosa increases its resistance to damage caused by aspirin during repeated administration of aspirin. Jin et al 69) observed that the increase in HSP (mainly HSP70) expression correlated with mucosal resistance that observed after repeated administration of aspirin.…”
Section: -1 Expression Of Hsps In Gastrointestinal Tractmentioning
confidence: 99%
“…Gastric adaptation to aspirin (ASA), i.e., resolution of mucosal damage despite continued exposure to the drug, is well documented (Graham et al, 1983;Ivey, 1988; J.W. Konturek et al, 1994; S.J. Konturek et al, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Direct damage of mucosal cells, reduction of prostaglandin formation and-although discussed controversially-reduced microcirculation contribute to the deleterious effects of NSAIDs on gastroduodenal mucosa (Graham et al, 1983;Ivey, 1988;J.W. Konturek et al, 1994; S.J.…”
Section: Introductionmentioning
confidence: 99%
“…This is in keeping with the lesser degree of injury caused by the aspirin dose used in this study compared with the other more extensive injury models. Similarly, measurable increases in TGF-␣ and epidermal growth factor also occur in adapted stomachs only after multiple doses of aspirin and not after a single injurious dose (Doljanin et al, 1996;Konturek et al, 1994aKonturek et al, , 1998aRomano et al, 1996). It is possible that the increments in mucosal RegI (and indeed TGF-␣ and epidermal growth factor) that occur as a result of each adapting dose finally culminate as an "effective" increase only after several episodes of daily injury-this would help to explain the lag time of several days required for the onset of adaptation St John et al, 1973;Wallace et al, 1995).…”
Section: Alderman Et Almentioning
confidence: 99%
“…Several studies in both humans and experimental animals using histologic assessments and incorporation of 3 [H]thymidine and bromodeoxyuridine conclude that enhanced proliferation likely contributes to the mechanism of reduced injury that is characteristic of gastric mucosal adaptation (Baumgartner et al, 1986;Eastwood and Quimby, 1982;Konturek et al, 1994a;Lev et al, 1972;Levi et al, 1992;Romano et al, 1996;Shorrock et al, 1990). A role A, mRNA expression of regenerating protein (RegI) and its receptor (Regr) in the gastric mucosa of control, single-dose, and adapted rats 4 hours after the last dose of vehicle or aspirin.…”
Section: Alderman Et Almentioning
confidence: 99%